Grundlage der Behandlung ekzematöser Erkrankungen im HNO-Bereich - Fölster-Holst, Regina; Albrecht, Tobias (HNO, 2017)
According to Coombs and Gell, cell-mediated immune responses belong to type IV reactions and are borne mainly by T lymphocytes. The eliciting allergens are usually so-called haptens. Haptens are substances which develop to whole antigens only by binding to protein carriers. In otorhinolaryngology, delayed allergic hypersensitivities are apparent mainly as contact eczemata. Facial dermatitis, auricle and ear canal eczema as well as perioral eczema belong to the most common forms of contact dermatitis in ENT patients. The patient’s medical history and morphology of the eczema give a strong indication for a proper diagnosis. Verification is carried out by patch test according to the Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften (AWMF, The Association of the Scientific Medical Societies in Germany) guidelines. Hereby the most widespread contact allergens are tested in a so-called “standard block”, which can be reduced to an individualized allergen spectrum, based on medical history. For therapy, allergen avoidance is the most important measure which should also be applied prophylactically. Moreover, antiinflammatory treatment of the contact eczema is carried out with tapering topical corticosteroids. Depending on the patient’s age, location and severity of the contact eczema, newer class II or III preparations should be chosen. Skin care preparations are helpful to reduce corticosteroid consumption and are indicated additionally after the acute phase treatment. An important differential diagnosis of contact eczema is atopic dermatitis. Whilst contact dermatitis experiences healing by avoiding the triggering noxious agent, genetically determined atopic dermatitis shows a chronic, recurrent course. In addition to topical corticosteroids, calcineurin inhibitors have been approved for treatment of atopic eczema. In all eczema diseases, regular skin care is a necessary measure which contributes mainly to barrier repair.